2001
DOI: 10.1111/j.1744-7429.2001.tb00162.x
|View full text |Cite
|
Sign up to set email alerts
|

Refuse to Refuge: Dry Season Use and Modification of Cattle Dung by Subterranean Termites in Guanacaste, Costa Rica1

Abstract: Baits and soil cores were used to quantify temporal variation in the use of cattle dung by two species of subterranean termites, Amitermes beaumonti Banks and Hoplotermes sp. nov. (hereafter referred to by genus), during the 1991 dry season in Guanacaste, Costa Rica. The densities of termite foragers of both species were evaluated in cattle dung patches (baits), in the soil beneath each patch (litter, 0–3.5 cm, and 3.5–7 cm), and in the same layers from adjacent dung‐free control sites. Dung patch and control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…Gould et al (2001) found Amitermes beaumonti to be more abundant in the stratum ranging from 0-3.5 cm below the cattle dung baits they used in Costa Rica (vs. the 3.5-7.0 cm stratum). Exactly the opposite pattern was found in control areas, indicating that at least this termite species adjusts its subterranean foraging behaviour according to the accessibility of dung.…”
Section: Impacts On Nutrient Cyclingmentioning
confidence: 99%
“…Gould et al (2001) found Amitermes beaumonti to be more abundant in the stratum ranging from 0-3.5 cm below the cattle dung baits they used in Costa Rica (vs. the 3.5-7.0 cm stratum). Exactly the opposite pattern was found in control areas, indicating that at least this termite species adjusts its subterranean foraging behaviour according to the accessibility of dung.…”
Section: Impacts On Nutrient Cyclingmentioning
confidence: 99%
“…Termites in the thatch-mound soil had cellulose food sources covering the ant nest, providing a more conducive foraging location compared with the bare-soil mounds. In addition, the study site was being used for grazing, and cattle dung is a known cellulose resource that is used by subterranean termites (Ferrar and Watson 1970, Gould et al 2001).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, dung beetles, due to their narrow thermal tolerances, cannot cope with the drastic temperature and humidity changes characteristic of deforested habitats (Barragán et al, 2014;Gómez-Cifuentes et al, 2017); a third possible explanation is fiber, the main component of dry cattle dung (Holter, 2016) that could act as an extra source of grass and litter and thus attract termites; and finally, dung may provide termites with nitrogen to supplement their low-nitrogen diet (Higashi et al, 1992). Although there is no information on the interaction between dung beetle and termites, the small number of samples colonized by both insects suggests that they may be mutually exclusive (Gould et al, 2001).…”
Section: Discussionmentioning
confidence: 99%